Stigma Peserta Didik terhadap Guru BK: Dampak terhadap Konseling dan Etika Profesional - Alvia Rahmadzani; Maya Rahadian Septiningtyas; Lobby Loekmono (CV. ITTC INDONESIA, 2026)
Students' perception of school guidance and counseling (BK) teachers in Indonesia remains marked by persistent negative stigma, with BK teachers often labeled as